A systematic review of body contouring surgery in post‐bariatric patients to determine its prevalence, effects on quality of life, desire, and barriers. (9th February 2021) - Jiang, Zhiyuan; Zhang, Guixiang; Huang, Jinming; Shen, Chaoyong; Cai, Zhaolun; Yin, Xiaonan; Yin, Yuan; Zhang, Bo
Summary: Many post‐bariatric patients have impaired health‐related quality of life (HRQoL) due to excess skin following weight loss; however, it is inconclusive whether body contouring surgery (BCS) improves this impairment. We aimed to comprehensively summarize existing evidence of the effect of BCS on the HRQoL (primary outcome) and determine the prevalence of, the desire for, and barriers to BCS (secondary outcomes). Randomized controlled trials, cohort, cross‐sectional, case–control, and longitudinal studies were systematically searched in PubMed, Embase, the Cochrane Central, and Web of Science. After screening 1923 potential records, 24 studies (representing 6867 participants) were deemed eligible. Only 18.5% of respondents from cross‐sectional studies underwent BCS, with abdominal BCS as the most common procedure. Most participants desired BCS but listed "cost" and "lacking reimbursement" as the main barriers. Results suggest that most post‐bariatric patients who underwent BCS experienced improvements in their HRQoL, which could be seen in almost every dimension evaluated, including body image and physical and psychosocial functions. Therefore, both bariatric and plastic surgeons should regard BCS not only as an aesthetic supplement but also as a vital part of functional recovery in the surgery‐mediated weight loss journey and, thus, provide it to more post‐bariatric patients.